Williams Syndrome with severe sensorineural hearing loss - (:unkn) unknown (MEDITERRANEAN SOC OTOLOGY & AUDIOLOGY, 2008)
Williams or Williams -Beuren Syndrome (WS) is a very rare syndrome associated with a microdeletion on chromosome 7q11.23. Williams syndrome is characterized by multiple congenital anomalies including distinctive facial features, cardiovascular anomalies, neurodevelopmental delay and mental retardation. Sensorineural hearing loss is not reported very often in WS patients. The purpose of the study is to present a Williams syndrome patient with severe sensorineural hearing loss. Bilateral severe sensorineural hearing loss was diagnosed in a child of 4 years old with WS. The child was fitted with binaural hearing aids and began to receive auditory habilitation. The child benefited from the amplification. Audiological evaluation is recommended for children with multiple anomalies including WS in order to prevent the harmful effects of the hearing loss.
Keywords: SUPRAVALVULAR AORTIC STENOSIS; HYPERACUSIS; ADULTS